Dead reckoning [large type] - Blakely, Mike (Wheeler Publishing, a part of Gale, a Cengage Company, 2018)
After a botched confidence scam, swindler Dee Hassard begins a killing spree that covers half of the Colorado Territory. His first victim is the brother of rustler-turned-preacher Carrol Moncrief. Now Carrol must fall back on his former outlaw savvy to track the murderer down. As the manhunt drifts mysteriously toward a legendary wilderness landmark known as the Mount of Snowy Cross, it embroils a number of men and women whose lives it will change forever. In the final reckoning, either the preacher or the killer must go to his dusty death. --Amazon